The effect of the pandemic on autoantibody rates in the general population - Mehmet Karabey,; Havva Kaya,; Alperen Ceylan,; Kadir Kaba,; Mehmet Özdemir,; Bahadır Feyzioğlu, (Archives of Rheumatology, 2024)
Objectives: The study aimed to investigate the possible effects of coronavirus disease 2019 (COVID-19) on autoantibodies. Patients and methods: Samples of 89,108 individuals (29,033 males, 60,075 females; median: 36 years; range, 0 to 96 years) who underwent autoimmune testing between January 2017 and May 2022 were retrospectively analyzed. The prepandemic period was defined as May 1, 2017, to March 20, 2020, while the pandemic period was defined as March 20, 2020, to May 31, 2022. Results: Of the participants, 0.55% were of foreign nationality. The positivity rate was 18.12%. Autoantibody positivity rates, when analyzed by sex, were higher in females for antinuclear antibody (ANA), antimitochondrial antibody (AMA), anti-liver kidney microsomal (LKM) antibody, immunoglobulin A (IgA) anti-gliadin antibody, anti-endomysial antibody A, anti-ribosomal P protein antibody, anti-Sjögren’s syndrome A (anti-SSA), anti-Sjögren’s syndrome B (anti-SSB), anti-Smith/ribonucleoprotein (anti-SM/RNP), anti-SM, and c-ANCA (cytoplasmic antineutrophil cytoplasmic antibody). When the prepandemic period was compared with the pandemic period, AMA, anti-LKM antibody, IgA anti-gliadin antibody, anti-endomysial antibody A, and anti-SM/RNP levels were higher in the prepandemic period, while ANA was higher during the pandemic. Additionally, statistically significant differences were found in the distributions of ANA, AMA, anti-LKM antibody, IgA anti-gliadin antibody, anti-endomysial antibody A, anti-ribosomal P protein antibody, anti-SM, anti-SSA, and c-ANCA across the years. Conclusion: This study could not establish a cause-effect relationship between the changing autoantibody levels during the COVID-19 pandemic and severe acute respiratory syndrome coronavirus 2 infection due to the lack of results from the same patients across different periods. Nonetheless, we believe the quantitative seroprevalence changes in such a large sample of autoantibody screening results over a five-year period, including the pandemic, are valuable.